2017
DOI: 10.1186/s13065-017-0342-9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of brazilin and protosappanin B in Caesalpinia sappan by ionic-liquid dispersive liquid-phase microextraction method combined with HPLC

Abstract: The conditions of heating, ionic liquid-based ultrasonic-assisted extraction combined with reverse-phase high performance liquid chromatography were optimized to simultaneously isolate and determinate brazilin and protosappanin B in Caesalpinia sappan. Ionic liquids, including [BMIM]Br, [BMIM]BF4, [BMIM]PF6 and [HMIM]PF6, were selected as extraction solvents while methanol, acetone, acetonitrile, ethanol and water were selected as dispersants. The chromatographic column was Purospher star RP-C18 (250 mm × 4.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…As ionic liquid is the core factor of this experiment, it is extremely important to select the suitable ionic liquid type. In our previous study [24,25,26,27,28,29], four imidazole ILs ([BMIM]BF 4 (1-Butyl-3-methylimidazolium tetrafluoroborate), [BMIM]Br(1-butyl-3-methylimidazolium bromide), [BMIM]PF 6 (1-butyl-3-methylimidazolium hexafluorophosphate), and [HMIM]PF 6 (1-Hexyl-3- methylimidazolium hexafluorophosphate)) could obviously improve the extraction yield. It was probably because of its stronger multi-interactions including π–π, ionic/charge–charge, and hydrogen bonding with those compounds [30].…”
Section: Resultsmentioning
confidence: 99%
“…As ionic liquid is the core factor of this experiment, it is extremely important to select the suitable ionic liquid type. In our previous study [24,25,26,27,28,29], four imidazole ILs ([BMIM]BF 4 (1-Butyl-3-methylimidazolium tetrafluoroborate), [BMIM]Br(1-butyl-3-methylimidazolium bromide), [BMIM]PF 6 (1-butyl-3-methylimidazolium hexafluorophosphate), and [HMIM]PF 6 (1-Hexyl-3- methylimidazolium hexafluorophosphate)) could obviously improve the extraction yield. It was probably because of its stronger multi-interactions including π–π, ionic/charge–charge, and hydrogen bonding with those compounds [30].…”
Section: Resultsmentioning
confidence: 99%
“…The color of the brazilin standard in [BMIM]Br was more concentrated due to bromide anions (Br − ), which can make ionic solutions more acidic than other anions (Anderson et al, 2002). The weak acidic ionic solution provides an advantage in extracting brazilin (Xia et al, 2017).…”
Section: Determination Of Brazilin In the Extract By Hplc Analysismentioning
confidence: 99%
“…While temperature, time, solid to liquid ratio, and solvent selection are reported to be the main influential parameters that can affect the UAE performance, polar solvents have been reported to be the suitable solvents for the extraction of phenolic compounds like brazilin. Based on their investigations through comparison of several solvents to extract brazilin from sappanwood heartwood, namely water, methanol, ethanol, acetonitrile, and acetone, Xia et al reported that methanol and water are the most suitable solvents [15]. Unfortunately, methanol is more toxic, expensive, and may cause serious environmental issues.…”
Section: Introductionmentioning
confidence: 99%